Analisis Dampak Fluktuasi Pasar Terhadap Strategi Penyesuaian Portofolio Investasi - Ika Lista Fadila; Wiwin Wulan; Revilia Nur Intan; Alimatun Nasyifa; Gusganda Suria Manda (LPPM Politeknik Pratama, 2026)
This study aim This study conceptually examines the impact of market fluctuations on portfolio adjustment strategies within increasingly volatile market conditions. Shifting market dynamics compel investors to review and modify their asset composition regularly to maintain portfolio performance and manage risk. Through a literature-based approach, this study highlights how volatility shapes risk perception, investment preferences, and portfolio adjustment decisions, including diversification, rebalancing, and the use of hedging instruments. The findings indicate that market fluctuations play a crucial role in determining the level of adaptation required in both short-term and long-term investment strategies. The theoretical contribution of this study lies in formulating a conceptual framework that explains the systematic relationship between market dynamics and portfolio adjustment mechanisms, providing a foundation for developing investment strategies that are more responsive to ongoing market changes.